Characteristics and Potential Use of Guava (Psidium Guajava L) for Processing of Concentrate - Yusof, Salmah (1989)
Studies were conducted to determine the characteristics of guava (Psidium guajava L) cv. Vietnamese of its potential use for processing it into guava concentrate. A maturity study showed that the guava took 16 weeks to reach maturity. The best indices of maturity were size, moisture, sugars and tannin contents. The moisture content at the mature stage was 94%. The fructose ,glucose and sucrose contents were 2.02%, 1.08% and 1.54%,respectively. The tannin content in the matured guava was low (37.0 mg/10gm sample) but the vitamin C content was high (76mg/100g sample). The structure of stone cells in guava fruits were examined microscopically. The stone cells became more prominent with increase in fruit maturity,hence the prepared puree were pulverised in order to improve its texture. Studies on the quality of puree produced from fruits at different stages of maturation showed that a puree of desireable quality was obtained from fruit sat the yellow green stage (stage 4). Artificial ripening was necessary to soften the fruits to make them ideal for processing into concentrate or puree.Fruit sat the yellow green stage had an increase in soluble pectin content to 67%. This increased the viscosity of puree . The vitamin C content also increased from 79.7mg-131.1mg/l00g sample. The puree showedless tendency to turn brown due to the low tannin contents(21mg/10g samples).